Stakeholder Perspectives on Risk Evaluation in Public-Private Partnership (PPP) Projects: A Comprehensive Analysis (International Journal of Food and Nutritional Sciences, 2022)
Large-scale infrastructure development has seen a rise in the use of public-private partnership (PPP) projects, which combine the advantages of both the public and private sectors. However, the intricacy of risk allocation and management, which is made more difficult by the many goals and interests of the parties involved, often poses a hurdle to the success of these initiatives. This study explores the complex process of risk assessment in public-private partnership (PPP) projects from the viewpoints of important stakeholders, such as governmental bodies, businesses operating in the private sector, financial institutions, and the general public.